Pengembangan Bakat Kepemimpinan Santri Melalui Kegiatan Organisasi Santri Darunnajah Cipining (OSDC) Pondok Pesantren Darunnajah 2 Cipining Bogor - Risyandi, Meidy; Zahir, Musthafa; Farid, Ahmad; Saputra, Yogi; Pratama, Arizqi Ihsan (Indo-MathEdu Intellectuals Journal, 2024)
a leadership crisis in the world of education that has not been able to be developed properly, so that educational goals have not been achieved. One of the reasons is that educational institutions (schools) do not pay proper attention to the development of students' talents and interests, especially in OSDC (extracurricular) activities. This research aims to describe OSDC violations and various activities that support the development of student leadership talents at PONPES Darunnajah 2. Qualitative research methods commonly used to obtain data are interviews, observation, and use of documentation. Research results: The OSIS at PONPES Darunnajah 2 is called the Darunnajah Cipining Santri Organization (OSDC). teachers in educating students from waking up until going back to sleep. OSDC is a means for students to develop their leadership talents through various activities at OSDC, various OSDC are: muhadoroh, scouts, committees for various events, as well as management in dormitories. PONPES Darunnajah 2 in carrying out its educational process is based on the five souls of PONPES, namely: the soul of sincerity, the spirit of simplicity, the spirit of independence, the spirit of Islamic ukhuwah, and the spirit of freedom